ANALYSIS OF HOUSEKEEPING SERVICE QUALITY IMPROVEMENT USING A LEAN SERVICE APPROACH AT PT XYZ - Abdurrahman; Heru Darmawan; Rani Rahmadiyani (PT. Radja Intercontinental Publishing, 2026)
The hospitality industry faces increasing demands for service quality improvement due to customer expectations for fast, consistent, and high-quality services. The housekeeping department has an important role in maintaining guest satisfaction because it is directly related to room cleanliness, comfort, and readiness. This study aims to analyze waste in the housekeeping service process and formulate improvement recommendations using the Lean Service approach at PT XYZ. This research used a descriptive qualitative method with data collection conducted through observations of Room Attendant activities, interviews with housekeeping staff and supervisors, and work process documentation. The analysis was carried out using process mapping, classification of value added, necessary non value added, and non value added activities, waste identification, and fishbone diagrams. The results showed that the housekeeping process still contained several main wastes, including waiting due to limited linen availability, unnecessary motion caused by searching for equipment, transportation due to movement to storage areas, and overprocessing caused by repeated activities. The discussion indicated that these wastes were influenced by human factors, work methods, materials, and work environment, requiring improvements through trolley standardization, linen management, and staff competency development. This study concludes that the Lean Service approach can improve the effectiveness of housekeeping work processes and support the enhancement of hotel service quality.